Membrane‐Mediated Protein–Protein Interactions of Cholesterol Side‐Chain Cleavage Cytochrome P450 with its Associated Electron Transport Proteins. Issue 9 (22nd July 2016) - Kubeil, Clemens; Yeung, Joyee Chun In; Tuckey, Robert C.; Rodgers, Raymond J.; Martin, Lisandra L.
Abstract: Cytochrome P450scc (P450scc or CYP11A1) catalyses the first enzymatic step of steroid biosynthesis, the cleavage of the side chain of cholesterol to produce pregnenolone in the mitochondrion. The activity of P450scc is dependent upon electron delivery from NADPH‐dependent adrenodoxin reductase (AdR), via adrenodoxin (Adx), to the P450scc. However, despite the structural and kinetic data that supports the mechanism by which Adx shuttles electrons one at a time between AdR and the P450scc, there are limited data available on the influence of the lipid membrane on these essential interactions. In this paper, the protein–membrane interactions between P450scc and its redox partners were examined on 1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphocholine (DMPC) membranes containing cholesterol (20 %), using a quartz crystal microbalance with dissipation monitoring. P450scc showed strong binding to these membranes, whereas AdR and Adx both showed weaker association. If pre‐mixed, all three proteins bound independently to the membrane layer in a distinctive two‐stage process, as observed by frequency changes upon binding. Concomitant changes in the dissipation revealed specific protein–protein interaction occurs upon reaching a critical concentration of proteins in the membrane layer. These changes were specific for the binding of the three pre‐mixed proteins and were not observed for a binary mixture of P450 and Adx, or sequential binding of the three proteins. A simple model was developed for the binding of all three proteins in a 1:1:1 mixture to the membrane and reproduces the experimental data describing the interaction of P450scc with the other proteins (AdR and Adx) after initial binding of the individual proteins. Thus, we conclude that the lipid membrane assists in the assembly of electron transport proteins and the activity of P450scc by providing a surface for the localised concentration of proteins, enabling them to act together as a metabolon. Abstract : It′s bound to work : A simple model for the interactions between P450scc, adrenodoxin, and adrenodoxin reductase at 1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphocholine membranes containing cholesterol has been developed using a quartz crystal microbalance with dissipation monitoring (see figure). A functional role is proposed for the inner mitochondrial membrane in cholesterol side‐chain cleavage by providing a 2D platform for the key proteins to assemble into a metabolon complex.